ANALISIS KADAR FLAVONOID PADA TEH DAUN LAMUN (Enhalus acoroides) BERDASARKAN TINGKAT KETUAAN DAUN - Harfalien Tehubijuluw; Theopilus Watuguly; Prelly M.J Tuapattinaya (BIOPENDIX, 2018)
Background: Seagrass (Enhalus acoroides) is a flowering plant (Angiospermae) that has fully adapted to life immersed in the sea. Seagrass is also a commodity that has been used by many people both modern and traditional. Traditionally seagrass has been used for compost and fertilizer, cigars and children's toys, made into baskets, some are eaten, and made into fishing nets. Whereas in the modern way is as a filter of waste, food, medicines, materials for paper mills, and sources of chemicals. Methods: Measurement of flavonoid levels of seagrass leaf tea (Enhalus acoroides) was analyzed using a one-way anava test. This research was conducted on 10-18 July 2018. Results: The analysis showed that old tea drinks from seagrass leaves (Enhalus acoroides) had high flavonoid levels of 0.1623% while half-old tea drinks with seagrass leaves had moderate flavonoid levels of 0.1263%. Conclusion: Young tea drinks using seagrass leaves (Enhalus acoroides) have lower flavonoid levels of 0.0888%